The cumulative impact of tidal stream turbine arrays on sediment transport in the Pentland Firth. (August 2015) - Fairley, I.; Masters, I.; Karunarathna, H.
Abstract: This contribution investigates the impact of the deployment of tidal stream turbine arrays on sediment dynamics and seabed morphology in the Pentland Firth, Scotland. The Pentland Firth is arguably the premier tidal stream site in the world and engineering developments are progressing rapidly. Therefore understanding and minimising impacts is vital to ensure the successful development of this nascent industry. Here a 3 dimensional coupled hydrodynamic and sediment transport numerical model is used to investigate the impact on sediment transport and morphodynamics of tidal stream arrays. The aim of the work presented here is twofold: firstly to provide prediction of the changes caused by multiple tidal stream turbine array developments to some of the unique sandy seabed environments in the Pentland Firth and secondly as a case study to determine the relationship between impacts of individual tidal stream farms and cumulative impacts of multiple farms. Due to connectivity in tidal flow it has been hypothesized that the cumulative impact of multiple arrays on sediment dynamics might be non-linear. This work suggests that, for the Pentland Firth, this is not the case: the cumulative impact of the 4 currently proposed arrays in the area is equal to the sum of the impacts of the individual arrays. Additionally, array implementation only has minimal effect on the baseline morphodynamics of the large sandbanks in the region, smaller more local sandbanks were not considered. These two results are extremely positive for tidal stream developers in the region since it removes the burden of assessing cumulative impact from individual developers and suggests that impacts to sub-sea morphodynamics is insignificant and hence is unlikely to be an impediment to development in the Pentland Firth with the currently proposed levels of extraction. Highlights: Maps of sediment coverage in the Pentland Firth are derived from multibeam data. Sediment transport in the Pentland Firth is modelled with and without arrays. Minimal impacts of energy extraction to the considered sandbanks are observed. Impacts on morphodynamics caused by multiple arrays are additive.